EKSPERIMENTASI MODEL PEMBELAJARAN DISCOVERY LEARNING (DL) DAN PROBLEM BASED LEARNING (PBL) PADA MATERI BANGUN RUANG DITINJAU DARI KEMANDIRIAN BELAJAR SISWA KELAS VIII SMP NEGERI SE-KABUPATEN BANYUMAS - Tito Kurniawan, Sandhy Prasetyo; Usodo, Budi; Subanti, Sri (Jurnal Pembelajaran Matematika, 2015)
Abstract: The aim of the research was to determine the effect of learning models on mathematics achievement viewed from learning independency. The learning models compared were direct Learning, DL, and PBL. This was quasi-experimental research with 3x3 factorial design. The population were all students of Junior High School in Banyumas. The samples were the students of SMPN 1 Patikraja, SMPN 2 Patikraja, and SMPN 2 Kalibagor, taken by using stratified cluster random sampling technique. The instruments used were mathematics achievement test and learning independency. The data were analyzed by two ways anova. Based on the data analysis, it can be concluded as follows. (1) The students treated with DL and PBL learning models provided better learning achievement than those treated with Direct learning model. The students treated with DL had mathematics learning achievement equal to those treated with PBL. (2) The students treated with high learning independency and medium learning independency provided better learning achievement than those treated with low learning independency. The students with high learning independency had learning achievement equal to those with medium independency. (3) In each learning independency group of students, DL and PBL learning models provided better achievement than the Direct one, and DL learning model provided learning achievement equal to the PBL learning model did. (4) In each learning model, the students treated with high learning independency and medium learning independency provided better learning achievement than those treated with low learning independency. The students with high learning independency had learning achievement equal to those with medium independency.Keywords: Discovery Learning, Problem Based Learning, Direct Learning, Learning IndependencyÂ